The Advantages of Proximity: Comparing Higher Education Policy in Scotland and Catalonia. Issue 1 (1st January 2016) - Busetti, Simone; Dente, Bruno
Abstract: The article claims that, following devolution, increased proximity will increase policy capacity by changing the form of policymaking and providing greater scope for policy tailoring. The hypothesis is tested against devolution of higher education responsibility in Scotland and Catalonia. Results show that devolution did not entail the development of the same form of policymaking in the two regions, but it nonetheless permitted the implementation of policies and tools that were both in contrast with global trends in higher education policy.